Historical dictionary of United States-Middle East relations - Hahn, Peter L. 1960- (Rowman & Littlefield, 2016)
This second edition of Historical Dictionary of United States-Middle East Relations contains a chronology, an introduction, appendixes, and an extensive bibliography. The dictionary section has over 300 cross-referenced entries on national leaders, non-governmental organizations, policy initiatives, and armed conflicts, as well as entries on such topics as intelligence, immigration, and weapons of mass destruction. This book is an excellent access point for students, researchers, and anyone wanting to know more about the US and Middle East Relations
Includes bibliographical references
Keywords: Außenpolitik; Naher Osten; USA; Middle East -- Foreign relations -- United States -- Dictionaries; United States -- Foreign relations -- Middle East -- Dictionaries; Mittlerer Osten; Wörterbuch